Approach for the Preparation of Various Classes of Peroxides Based on the Reaction of Triketones with H2O2: First Examples of Ozonide Rearrangements. Issue 32 (2nd July 2014) - Yaremenko, Ivan A.; Terent'ev, Alexander O.; Vil', Vera A.; Novikov, Roman A.; Chernyshev, Vladimir V.; Tafeenko, Viktor A.; Levitsky, Dmitri O.; Fleury, Fabrice; Nikishin, Gennady I.
Abstract The reaction of β, δ‐triketones with an ethereal solution of H2O2 catalyzed by heteropoly acids in the presence of a polar aprotic co‐solvent proceeds via three pathways to form three classes of peroxides: tricyclic monoperoxides, bridged tetraoxanes, and a pair of stereoisomeric ozonides. The reaction is unusual in that produces bridged tetraoxanes and ozonides with one of the three carbonyl groups remaining intact. In the synthesis of bridged tetraoxanes, the peroxide ring is formed by the reaction of hydrogen peroxide with two carbonyl groups at the β positions. The synthesis of ozonides from ketones and hydrogen peroxide is a unique process in which the ozonide ring is formed with the participation of two carbonyl groups at the δ positions. Rearrangements of ozonides were found for the first time after more than one century of their active investigation. Ozonides are interconverted with each other and rearranged into tricyclic monoperoxides, whereas ozonides and tricyclic monoperoxides are transformed into bridged tetraoxanes. The individual reaction products were isolated by column chromatography and characterized by NMR spectroscopy, mass spectrometry, and elemental analysis. One representative of each class of peroxides was characterized by X‐ray diffraction.